A new highly digestible prescription diet containing Bacillus velezensis DSM 15544, fructo-oligosaccharides, plasma immunoglobulin, yeast and sepiolite for the management of acute diarrhea in dogs—a randomized double-blinded, controlled trial - Jeusette, I.; Apper, E.; Fragua, V.; Sanchez, N.; Torre, C.; Badiella, L.; Puig, J.; Ballester, E.; Jurado, A.; Feo Bernabe, L. (Frontiers in Veterinary Science, 2025)
ObjectiveTo determine if a newly formulated diet with safe and highly digestible ingredients, Bacillus velezensis DSM 15544, fructo-oligosaccharides, animal plasma protein, dried whole yeast and sepiolite contributes toward the management of canine acute diarrhea.HypothesisThe new diet (Diet B) will reduce the time to achieve normal fecal consistency compared to a highly digestible control (Diet A).MethodsMulticenter randomized, double-blinded, parallel-designed study with adult dogs with mild to moderate acute signs (less than 7 days) of uncomplicated diarrhea as inclusion criteria. Exclusion criteria were history of gastrointestinal signs, lack of correct vaccination and deworming, abnormal ultrasound examination, and previous administration of antibiotics, omeprazole or nutritional supplement. Response variables were compared using the appropriate bivariate test, time to recovery was analyzed using survival analysis techniques.ResultsOne hundred eleven dogs finished the study. Dogs fed Diet B (n = 56) had a quicker recovery time of fecal consistency compared to A (3.6 ± 0.9 vs. 5.9 ± 0.9 days). Fecal frequency and odor were also quickly restored compared to diet A. Survival analysis confirmed a 1.6 times greater chance of recovery with Diet B compared to diet A. Feeding Diet B also improved dysbiosis index at recheck compared to diet A (−1 ± 3 vs. 0.65 ± 3).ConclusionDiet B resulted in faster clinical resolution, improved fecal consistency, frequency, odor and reduced incidence of dysbiosis compared to Diet A, making it a superior dietary approach in the management of mild acute diarrhea in dogs.